Pengenalan Material Yang Digunakan Dalam Proses Pengelasan Berdasarkan Spesifikasi Material - Fathan Mubina Dewadi Fathan; Ramadhan Ronggo Jati; Bella Sofiyanti (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
In the Karawang area, there are numerous issues, one of which is that certain local communities have not gained professional competence that may be used to earn a living. This material welding course follows a straightforward procedure that includes preparation, process, and output. This training's preparation focuses on the equipment and materials required, as the availability of these items must be taken into account. With the application of this activity, university knowledge can be created in this community service activity, which can also help academic requirements as one of higher education's tridharma.